MONITORING OF THE AGRICULTURAL LANDS AND SOIL FERTILITY LEVEL OF THE REPUBLIC OF ADYGEA - Y. N. Ashinov; N. I. Mamsirov (Новые технологии, 2022)
According to the “Regulations on the implementation of state monitoring of lands”, approved by the Decree of the Government of the Russian Federation of November 28, 2002 No. 846, information is collected on the state of lands in the Russian Federation, processed and stored. Continuous monitoring of the use of lands is carried out on the basis of their intended purpose and permitted use, analysis and assessment of the qualitative state of land, taking into account the impact of natural and anthropogenic factors. Land monitoring is carried out by the federal executive authorities, the executive authorities of the constituent entities of the Russian Federation and local governments in accordance within their powers [1]. But, the ongoing monitoring does not provide the proper result for monitoring land plots and crop rotation fields as a production resource and is not carried out according to a number of parameters characterizing soil fertility that are essential for agricultural production. The specificity of accounting for agricultural lands as a natural resource used as the main means of production in agriculture requires different approaches and a wider list of indicators of the state of such lands and their fertility [2; 3]. In this regard, studies have been carried out to monitor agricultural lands and analyze the current state of the use of agricultural lands for effective agricultural production, and on its basis a comprehensive assessment of the ecological state of agricultural landscapes of the Republic of Adygea has been carried out. The authors have analyzed the state of agricultural lands at the present stage and identified possible ways of rational use of available crop lands. Factors limiting the placement of agricultural crops in specific areas of the republic and the reasons that reduce their productivity and product quality have also been established.